Recognition and assessment of atypical and ambiguous genitalia in the newborn. Issue 10 (25th April 2017) - Davies, Justin H; Cheetham, Timothy
Abstract : The baby with atypical or ambiguous genitalia is usually born in secondary care. For most clinicians, this is an unfamiliar and challenging scenario with the potential for life-long ramifications arising from a consultation led by an unprepared clinician. Language needs to be used carefully with particular clarity when liaising with parents, local health professionals and the specialist multidisciplinary team. Confidence in the recognition and assessment of atypical or ambiguous genitalia in a newborn will guide the local clinician when deciding on the initial investigations required and is a foundation for subsequent management. The local team have key roles in the initial support for parents as well as managing expectations at a time of great uncertainty. There are numerous different diagnoses that can result in atypical or ambiguous genitalia. The clinical findings should guide the initial investigations, and there are many pitfalls when it comes to interpreting the results. The aim of this article is to provide an initial approach to the management of a baby born with atypical or ambiguous genitalia.